2012
DOI: 10.3390/ijerph10010107
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models for Efficacy Testing of Agents against Radiation Carcinogenesis — A Literature Review

Abstract: As the number of cancer survivors treated with radiation as a part of their therapy regimen is constantly increasing, so is concern about radiation-induced cancers. This increases the need for therapeutic and mitigating agents against secondary neoplasias. Development and efficacy testing of these agents requires not only extensive in vitro assessment, but also a set of reliable animal models of radiation-induced carcinogenesis. The laboratory mouse (Mus musculus) remains one of the best animal model systems f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…Cancers arising from precursor or immature T cells developing within the thymus [ 15 ], presenting as massive clonal expansion of thymic T cells (with or without involvement of peripheral lymphoid organs), are one of the principal tumours induced in mice exposed to whole-body irradiation (reviewed in [ 16 ]). Although the incidence following irradiation varies across inbred mouse strains, T cell lymphomas (TL) generally have short latency (within 3–9 months following irradiation), occur infrequently in control mice, and show characteristic changes in one or more key tumour suppressor genes (TSG) or oncogenes [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancers arising from precursor or immature T cells developing within the thymus [ 15 ], presenting as massive clonal expansion of thymic T cells (with or without involvement of peripheral lymphoid organs), are one of the principal tumours induced in mice exposed to whole-body irradiation (reviewed in [ 16 ]). Although the incidence following irradiation varies across inbred mouse strains, T cell lymphomas (TL) generally have short latency (within 3–9 months following irradiation), occur infrequently in control mice, and show characteristic changes in one or more key tumour suppressor genes (TSG) or oncogenes [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that a lethal dose of radiation for 70% mice within 30 days (level of LD70/30) by total-body irradiation was 10.5–12 Gy [ 30 ]. Induction of leukemia in mice with ionizing radiation was reported at doses of 3–4.25 Gy [ 31 ]. Wernle et al reported that 5 Gy units of local irradiation to mice hind limb could significantly change the bone morphology and strength with time [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ex vivo human cell line radiation studies have explored cytogenic markers, nucleotide pool damage, and mutations [ 7 ] and showed significant changes in gene expression in response to radiation under heterogeneous experimental conditions [ 8 , 9 ]. Likewise, the limited radiation studies in animal models have been heterogeneous and demonstrated distinct changes in gene expression in various tissues [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%